Enhanced nondestructive characterization of ordinary chondrites using complex magnetic susceptibility measurements. (29th December 2017) - Oliver, P.; Ralchenko, M.; Samson, C.; Ernst, R. E.; McCausland, P. J. A.; West, G. F.
Abstract: Ordinary chondrites have previously been nondestructively characterized using bulk magnetic susceptibility, broadly reflecting their Fe‐Ni alloy content. We seek to expand the information that can be recovered from magnetic susceptibility by using the University of Toronto Electromagnetic Induction Spectrometer (UTEMIS) to measure the complex magnetic susceptibility tensor of 20 ordinary chondrites samples in addition to 16 Gao–Guenie (H5) chondrites at 35 frequencies from 90 Hz to 64 kHz, at variable low applied field strengths <10 A m −1 . Following removal of the field‐dependent component of susceptibility, frequency dependence, in‐ and out‐of‐phase components, and bulk magnetic susceptibility were interpreted. Most meteorites showed no frequency‐dependent in‐phase responses, but had a frequency‐dependent out‐of‐phase response attributed to eddy currents induced in conductive minerals. Greater in‐ and out‐of‐phase frequency dependence correlated with lower fayalite content in olivine and was, in turn, inversely proportional to Fe‐Ni alloy content. The uncertainty in the UTEMIS measurements ranges from approximately 0.05% for low‐frequency in‐phase measurements to a maximum of 3% for low‐frequency out‐of‐phase measurements. This uncertainty level was far lower than the intra‐meteorite variability for the Gao–Guenie suite suggesting inhomogeneity at scales of approximately 10 g.